Financial Ratios Analysis to Assess Financial Performance of Cement Companies that listed on Indonesia Stock Exchange 2017 – 2019 - Intan Yuni Sukmawati; Karnowahadi - Karnowahadi; Subandi - Subandi (JOBS (Jurnal Of Business Studies), 2022)
Financial ratios analysis to assess financial performance of cement companies that listed on Indonesia Stock Exchange. The company that listed on Indonesia Stock Exchange/go public need to pay to attention their financial performance to make investors interested. Object of the research are cement companies that listed on Indonesia Stock Exchange, there are: PT Indocement Tunggal Prakarsa Tbk (INTP), PT Solusi Bangun Indonesia Tbk (SMCB), PT Semen Baturaja (Persero) Tbk (SMBR) and PT Semen Indonesia (Persero) Tbk (SMGR). Financial performance in this research assessed by financial ratio method, there are liquidity ratio (Current Ratio & Quick Ratio), solvency ratio (Debt to Asset Ratio & Debt to Equity Ratio), profitability ratio (Return on Invesment & Return on Equity). The highest liquidity in 2017 until 2019 reached by PT Indocement Tunggal Prakarsa Tbk (INTP). The lowest solvency in 2017 until 2019 reached by PT Indocement Tunggal Prakarsa Tbk (INTP). The highest profitability in 2017-2019 reached by PT Indocement TunggaL Prakarsa Tbk (INTP). Assessed from liquidity in 2017 to 2019 shows PT Indocement Tunggal Prakarsa (INTP) was liquid. In 2017 to 2019, PT Semen Indonesia (Persero) Tbk (SMGR) was an illiquid based on the results of the current ratio, whereas based on the results of the quick ratio in 2017 and 2018 it was liquid but 2019 it decreased to become illiquid. PT Solusi Bangun Indonesia Tbk (SMCB) was illiquid, then, PT Semen Baturaja (Persero) Tbk (SMBR) was liquid in 2017 to 2019. Assessed from solvency in 2017 to 2019 shows PT Indocement Tunggal Prakarsa Tbk (INTP) was solvable, PT Semen Indonesia (Persero) Tbk (SMGR) was insolvable. PT Solusi Bangun Indonesia Tbk (SMCB) was insolvable. PT Semen Baturaja (Persero) Tbk (SMBR) was solvabel in 2017 while 2018 to 2019 was insolvable based on the results of the debt to aset ratio, but 2017 to 2019 was solvable based on the results of the debt to equity ratio